1997
DOI: 10.1002/(sici)1097-0177(199709)210:1<11::aid-aja2>3.0.co;2-4
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and developmental expression ofAmphiTob, an amphioxus homolog of vertebrateTob in thePC3/BTG1/Tob family of tumor suppressor genes

Abstract: Tob is a member of the PC3/BTG1/Tob family of vertebrate tumor suppressor genes; its expression is known to inhibit proliferation of cells in vitro, but its possible roles during normal development have not been investigated previously. The present study concerns the structure and developmental expression of AmphiTob in an invertebrate chordate, amphioxus. This is the first investigation of any Tob gene during embryological development. The 311 amino acid AmphiTob protein is similar to vertebrate Tob but lacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The other gene analyzed is tob‐1 , a member of the recently identified BTG family whose founder gene, BTG1 (B‐cell translocation gene 1), was firstly cloned near the breakpoint of a chromosomal translocation associated to a chronic lymphocytic leukemia [37]. A wealth of evidence suggests that Btg proteins may be mediators of multiple anti‐proliferative activities [28,37–40]. Particularly, Tob‐1 is involved in the arrest of cell cycle at G1/S boundary [28,39] and its expression varies during vertebrate development [40].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other gene analyzed is tob‐1 , a member of the recently identified BTG family whose founder gene, BTG1 (B‐cell translocation gene 1), was firstly cloned near the breakpoint of a chromosomal translocation associated to a chronic lymphocytic leukemia [37]. A wealth of evidence suggests that Btg proteins may be mediators of multiple anti‐proliferative activities [28,37–40]. Particularly, Tob‐1 is involved in the arrest of cell cycle at G1/S boundary [28,39] and its expression varies during vertebrate development [40].…”
Section: Resultsmentioning
confidence: 99%
“…A wealth of evidence suggests that Btg proteins may be mediators of multiple anti‐proliferative activities [28,37–40]. Particularly, Tob‐1 is involved in the arrest of cell cycle at G1/S boundary [28,39] and its expression varies during vertebrate development [40]. It was initially identified as a protein specifically interacting with ErbB‐2 growth factor receptor, and thus it might negatively regulate the proliferative activity of transmembrane protein kinases [28].…”
Section: Resultsmentioning
confidence: 99%
“…Another study showed a modification of APRO2 expression during myogenesis with an increase of its expression during the phase of differentiation of myoblasts into myotubes [23,34]. Finally, xBTG1 ( Xenopus ) and Amphitob ( Amphioxus ) play a role in the control of the embryonic development of these animals [5,35]. On the other hand, several experiments showed that the forced expression of these genes ( APRO1, APRO2, APRO3, APRO4, APRO5, APRO6 ) was more or less anti‐proliferative [3,4,7–9,18,35,36].…”
Section: Implication Of Apro Family Genes In Biological Processesmentioning
confidence: 99%
“…Although the respective approaches to discover the genes/molecules were different, a biological common feature of these gene products was their ability to inhibit cell proliferation. From that time on, other novel related genes were also isolated over the past years using different cloning strategies [5–10]. Since no homology to known functional motifs is evident in their protein sequences of them, it appears likely that these molecules belong to a novel functional class of cell cycle regulators.…”
Section: Introductionmentioning
confidence: 99%
“…The antiproliferative activity of this gene, called PC3 (for pheochromocytoma cell-3), and its involvement in cell-cycle regulation, were demonstrated more recently (10). It was also shown that overexpression of the Tob protein inhibits NIH 3T3 cell growth (11), and that its expression varies during amphioxus development (12). As for BTG3, its expression at the end of the G 1 phase has been detected in T lymphocytes (4).…”
mentioning
confidence: 99%